What should urologists know about evidence-based medicine? - Jan W Mazel; Rudolf W Poolman (Indian Journal of Urology, 2011)
Objectives: This article outlines the basic principles of evidence-based medicine (EBM) and provides urologists with some tools to further explore, understand, and work with EBM. Materials and Methods: A narrative review was conducted illustrating several aspects of EBM. Results: Based on the definition of EBM, the aspects of evidence are clarified and a systematic approach is presented for integrating the evidence with individual patient values and circumstances. Next, sources for finding the best evidence are described and misconceptions about EBM are corrected. Finally, the current state of EBM in urology is discussed. Conclusions: It is clear that EBM will have an increasing relevance for urologists. Therefore, it is essential that all urologists have an understanding of the fundamental principles of EBM.